Map of northern Alberta land districts : comprising agencies of Peace River, Grande Prairie & Edmonton - Lynch, F. C. C. (Francis Christopher Chisholm), 1884- (Department of the Interior Canada, 1919)
This map shows land districts and lot distribution in Northern Alberta in 1919, as well as number of vacant quarter sections in each township. "Showing number of quarter-sections in each township available for homestead entry". Scale 1:2,217,600, or 35 miles to 1 inch. Relief shown by spot heights. Includes notes. Shows land districts and lots. 3rd edition. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .